A Study of Social Memory and Forgetting by Paul Connerton: Mechanisms and Tools - Tetiana Kuprii (Cхід, 2024)
This research is dedicated to the phenomenon of social memory and its component, social amnesia, as revealed in the works of the British sociologist and philosopher Paul Connerton. The author explores the identified types of social forgetting in the researcher's concept, analyzes the factors that give rise to them, and the mechanisms and tools for including the phenomenon in the metaphysics of social being and reality. The study highlights the significant contribution of this renowned sociologist to the theoretical exploration of social memory, social time, and social amnesia as factors in historical processes and as sociocultural determinants of sociogenesis.) The process of reflection of societal forgetting is interpreted as a rejection or removal from social and cultural memory of a reliable social assessment of the significance of these phenomena and facts. Spontaneous manifestations of social amnesia are inevitable in history, periodically projecting in society the need to temporarily relieve itself of the weight of comprehensive historical memory and responsibility. In this case, it has a functional aspect, being one of the mechanisms of psychological self-defense of society. It has been shown how society and the state, driven by their own needs, utilize instruments of social preservation to structure and construct their memories, endowing them with new interpretations to address various objectives. Each generation independently reshapes collective memories of the past; some of these memories become prominent in the current generation's mentality, while others are suppressed and undergo amnesia. The study examines models of sociocultural reproduction, highlighting Paul Connerton's interpretation of the possibility of social forgetting in its contemporary forms. The author concludes that, whereas in ancient societies disruptions in social memory were primarily effected through the physical eradication of groups and the destruction of written records, the modern era's cultural framework inherently facilitates and necessitates discontinuities in social memory and social forgetting.